1979
DOI: 10.1128/aem.38.4.616-620.1979
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Some Properties of an Extracellular Amylase from a Moderate Halophile, Micrococcus halobius

Abstract: A moderate halophile, Micrococcus halobius ATCC 21727, produced an extracellular dextrinogenic amylase when cultivated in media containing 1 to 3 M NaCl. The amylase was purified from the culture filtrate to an electrophoretically homogenous state by glycogen-complex formation, diethylaminoethyl-cellulose chromatography, and Bio-Gel P-200 gel filtration. The enzyme had maximal activity at pH 6 to 7 in 0.25 M NaCl or 0.75 M KCI at 50 to 550C. The activity was lost by dialysis against distilled water. Molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 21 publications
6
27
0
1
Order By: Relevance
“…Similar results have been reported for most, mainly K-amylases [15], as described for enzymes produced by the moderate halophiles Nesterenkonia halobia or Acinetobacter spp. [6,7]. Regulation of production of extracellular enzymes in enteric bacteria proceeds at the transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported for most, mainly K-amylases [15], as described for enzymes produced by the moderate halophiles Nesterenkonia halobia or Acinetobacter spp. [6,7]. Regulation of production of extracellular enzymes in enteric bacteria proceeds at the transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Micrococcus sp. 4 amylase resembles the other reported moderately halophilic amylase from M. halobius (Onishi and Sonoda 1979) in some properties such as optimum temperature and action pattern on soluble starch but is novel in its salt requirement for production and activity. I t also produces a golden yellow pigment which is not reported in the case of M. halobius.…”
Section: Growth and Enzyme Productionmentioning
confidence: 54%
“…Recently, halophiles have also been extensively screened for production of various enzymes (Kamekura 1986) and checked for their biotechnological potential (Ramos-Cormenzana 1989). Moderately halophilic amylases have been reported to be produced by Micrococcus halobtus (Onishi 1972a, b ;Onishi and Sonoda 1979) and Actnetobacter sp. (Onishi and Hidaka 1978) where they are secreted in a medium containing sodium chloride or potassium chloride and require these salts for their activity.…”
Section: Introductionmentioning
confidence: 99%
“…The B. subtilis H 1 growth curve, monitored spectrophotometrically for 60 h, increased exponentially, and the specific activities of the a-amylase enzyme almost followed the same pattern, which may be due to the secretion of the intracellular enzyme during growth or to the presence of Ca ++ in the SGM that was added to stabilize the enzyme (Onishi and Sonoda 1979;Wahlstrom et al 2003). Growth and a-amylase syntheses by the W 20 mutant strain indicated that the stationary phase was achieved sooner than the parent culture (B subtilis H 1 ), and the specific activities of a-amylase exhibited a steady level between 36and 60-h incubation, which may be due to the genetic difference or to the lysis of the bacterial cells (Woo et al 2000;Vitakainen et al 2001).…”
Section: A-amylase Synthesis During Growth and Factors Involvedmentioning
confidence: 87%